Education for Resiliency: An Examination of Risks in a Native American Youth Environment - du Hamel Yellow Horn, Paula (2010)
Doctor of Education thesis awarded in 2009 from Charles Sturt University. The author has given permission to the Queen's University Education Library to add this thesis to the publications held in QSpace so that it can be freely searched and disseminated on the Web and used for educational purposes. This thesis examines Blackfoot (Kainai) Native youth risks in contemporary society including alcohol, drugs, and crime. The overall purpose of the thesis is to investigate and address environmental, social, physical, and mental issues associated with risks, in both their rural and urban environment for Kainai youth in Southern Alberta, Canada. The research and fieldwork conducted observes Native American Peoples, specifically Kainai youth risks, and explores resiliency and factors contributing to resiliency in support of Native American youth. Not only do I examine the individual, but I examine multiple variables and connections, including the community, to guide my analysis. My research framework is supported by Pierre Bourdieu’s theory of social realities - the ‘field’, ‘Habitus’, and ‘capital’. The research undertaken considers the social, cultural, and economic realities existing in Native American communities and therefore investigates what values are associated with them and the rationale behind their construction. More specifically, I examine Native American inter-generational traumas stemming from colonization violences, and, intragenerational traumas – Native American tendencies to incur self-violences and perpetuate continual cycles of violences. The purpose of this thesis is to identify the social realities of risk to help develop resiliency in Native American youth in contemporary Native American environments. Thus the research focuses not only on helping young peoples as individuals, but also on helping Native American communities and non-native communities to deal better with the consequences of colonization and assimilation practices of Native American Peoples (First Nations, Inuit, and Métis) in the ...